![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x^2-1\right)^3-\left(x^4+x^2+1\right)\left(x^2-1\right)=x^6-3x^4+3x-1-x^6+1=-3x^4+3x^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
có phải ý bạn là:
rút gọn biểu thức:
\(\frac{x}{\left(x+1\right)^3}\cdot\frac{1}{x+1}+\frac{1}{x^2+2x+1}\cdot\frac{1}{x^2+1}:\frac{x-1}{x^3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=\left(x-3\right)\left(x^2+1-x^2+1\right)\)
\(=\left(x-3\right).2\)
Học tốt
\(\left(x^2+1\right)\left(x-3\right)-\left(x-3\right)\left(x^2-1\right)\)
\(\left(x-3\right)\left(x^2+1-x^2-1\right)\)
\(\left(x-3\right)2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
3.(x^4+x^2+1)-(x^2+x+1)^2=3.(x^4+2x^2+1-x^2)-(x^2+x+1)^2
=3.((x^2+1)^2-x^2)-(x^2+x+1)^2
=3.(x^2+x+1)(x^2-x+1)-(x^2+x+1)^2
=(x^2+x+1)(3.(x^2-x+1)-(x^2+x+1)
=(x^2+x+1)(2x^2-4x+2)
=(x^2+x+1)(căn 2 .x- căn 2)^2
![](https://rs.olm.vn/images/avt/0.png?1311)